Balandra Bay, Trinidad, B.W.I. - (:unkn) unknown (My University, 2009)
A photo from a hill overlooking Balandra Bay on Trinidad's north east coast. The shoreline is gently sloping and backed by coconut, almond and sea grape trees.
Colour: Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Balandra Bay; Beaches--Trinidad and Tobago; Coasts--Trinidad and Tobago; Bays--Trinidad and Tobago